Population pharmacokinetics of haloperidol in terminally ill adult patients - Franken, L. G. (Eur J Clin Pharmacol, 2017)
PURPOSE: Over 80% of the terminally ill patients experience delirium in their final days. In the treatment of delirium, haloperidol is the drug of choice. Very little is known about the pharmacokinetics of haloperidol in this patient population. We therefore designed a population pharmacokinetic study to gain more insight into the pharmacokinetics of haloperidol in terminally ill patients and to find clinically relevant covariates that may be used in developing an individualised dosing regimen. METHODS: Using non-linear mixed effects modelling (NONMEM 7.2), a population pharmacokinetic analysis was conducted with 87 samples from 28 terminally ill patients who received haloperidol either orally or subcutaneously. The covariates analysed were patient and disease characteristics as well as co-medication. RESULTS: The data were accurately described by a one-compartment model. The population mean estimates for oral bioavailability, clearance and volume of distribution for an average patient were 0.86 (IIV 55%), 29.3 L/h (IIV 43%) and 1260 L (IIV 70%), respectively. This resulted in an average terminal half-life of haloperidol of around 30 h. CONCLUSION: Our study showed that the pharmacokinetics of haloperidol could be adequately described by a one-compartment model. The pharmacokinetics in terminally ill patients was comparable to other patients. We were not able to explain the wide variability using covariates.